Digital transformation of the world market of aviation services - F. Baykov (E-Management)
The article is devoted to the analysis of the key effects of digital transformation for the development of the modern world market of aviation services. The long-term international competitiveness of airlines will be determined by the use of a wide range of revolutionary technologies, new service delivery models, as well as the degree of “digitization” of key business processes.It has been established that the intensive development of the global passenger air transportation market is due to both demographic trends and the emergence of new generations of consumers. At the same time, the basic competitive advantage for airlines will be the degree of their digital maturity and the possibility of their investments in a personalized travel experience based on the use of new digital technologies. In this regard, relations between airlines and external contractors will be built in a new organizational context, as airlines will strive to provide greater flexibility for their business models.The digital transformation for airlines will mainly relate to the revision of the customer relationship system, emphasis on the “digital consumer”, and this trend will be strengthened by global digital platforms and online aggregators in the field of tourism. Comprehensive digital transformation projects are becoming increasingly important in corporate strategies of airlines. These projects, in particular, concern specialized innovative services, for example, air travel by subscription, creation of specialized corporate venture capital funds, conclusion of contracts of hybrid types.The study found that digital transformation in the global aviation services market is subject to many exogenous shocks, in particular, national law regulations that cannot adapt quickly after changes in the market. The main problem limiting the digital transformation of the industry remains the regulatory differences in countries regarding the requirements of confidentiality and data security.